Egy színházi előadás archeológiája: (Milo Rau: Orestes in Mosul) - Jászay, Tamás (Studia Litteraria, 2022)
“Oresteia is of course only an alibi to make Orestes in Mosul, a frame within which completely foreign things are complimented, in which the disparate biographical realities of the actors and the context for their own interest in the Oresteia can be shown” – says Swiss director-writer Milo Rau of his own unconventional adaptation of the Oresteia. The aim of the essay is to present Rau’s working method and to recall significant trends in the staging traditions of Aeschylus’s trilogy. Subsequently, through an analysis of Rau’s performance Orestes in Mosul (2019) and its related written and audiovisual documents, I aim to provide an introduction to a possible theatrical archaeology.